Effect of Active Learning Strategy Type Card Sort of Understanding The Concept of Students: (Quasi-Experimental Study in Elementary School Fourth Grade Cigedang on Scene 7 IPS Subtheme 1 Education Academic Year 2018/2019) - Sari, Mia Zultrianti; Camelia, Camelia (International Conference on Elementary Education, 2020)
Learning is a process of interaction or educational activities between teachers and students. Problems faced that students have difficulty in understanding the material presented by the teacher. Understanding the concept is needed by students in each lesson. Active learning strategy type of Card Sort is a student-centered learning with emphasis on active student involvement in learning that is used to make students better understand the concepts being taught. This study aimed to determine the effect of the use of Active Learning Strategies Card Sort mode and the differences increase in the understanding of the concept of students who get Type Active Learning Strategies Card Sort by students who had learning lectures. The method used is quasi experiments conducted at Elementary School fourth grade B Cigedang. To obtain the data used research instruments are objective tests (pretest-posttest). Data were analyzed using t tests to see the effect and the difference increased understanding of the concept of students in both groups. These results indicate that learning using Active Learning Strategies Type of Card Sort the experimental class has an average value of 87.29 posttest results, while the control class by using the average learning lecture 70.85 posttest results so that there are differences in the average value experiment grade higher than the grade control. T as well as on the group posttest is 7.795 with Î± = 0.05 so the H1 hypothesis is accepted by the acceptance criteria. It can be concluded that there are significant use of Active Learning Strategies Card Sort mode and the differences increase in the understanding of the concept of students in the fourth grade social studies learning Cigedang B Elementary School. To implement the strategy of active learning card types are advised to pay attention to the allocation sort of time available for learning remain effective and must pay attention to conditioning classes